A prospective study of the pattern of morbidity and medication use during antenatal and perinatal period in mothers of neonates admitted to neonatal intensive care unit of a tertiary care hospital - P., Anitha; Yashoda, H. T. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Most drugs taken by pregnant women can cross the placenta (except high molecular weight drugs like heparin) and expose the foetus to pharmacologic and teratogenic effects. The drugs used in the late antenatal and intranatal period may have a potential perinatal and neonatal outcome. Methods: The pattern of maternal morbidity and drug use was assessed prospectively in 150 consecutive mothers of neonates admitted to NICU. The number of drugs used, therapeutic class, dose, route, frequency and purpose of use were recorded. The efficacy and safety of medications was assessed by neonatal outcome. Results: The most common maternal morbidity during pregnancy was PIH, eclampsia, hypothyroidism, GDM, PROM, oligohydromnias, anemiaorpolyhydromnias, and 4% (n=6) had more than one complication. Different therapeutic classes of drugs were used as per the prevailing clinical conditions or complications. The total number of drugs used was 26, with an average of 3.68 per subject. AMAs were the most commonly used drugs, chosen empirically and used in combination for prophylaxis or control of infections. Other classes of drugs were used for specific indications. None of the NICU admissions in the present study seem to be related to antenatal or perinatal drug exposure. The treatment outcome was very good in most of the subjects and no drug related adverse events or interactions were observed. Conclusions: Maternal morbidity and drugs administered to mother play an important role in improving the neonatal outcome.